1999
DOI: 10.1097/00004872-199917070-00019
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of hypertension and the incidence of kidney stones in men

Abstract: Hypertension in middle-aged men is a significant predictor of kidney stone disease rather than a consequence of renal damage caused by the kidney stones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 25 publications
3
44
0
1
Order By: Relevance
“…Sofia NH et al also found that nephrolithiasis is more common in men than in women and is more prevalent between the ages of 20 to 40 in both sexes. coffee and tea, low in fibre, vegetable protein and unrefined carbohydrates are at increased risk of kidney stones, 20 our study also found that high salt, coffee and tea intake and non vegetarian diet, less intake of water is also common risk factors for urolithiasis. Similar to other studies, [19][20][21] we also found that Diabetic and Hypertension were other risk factors for renal calculi present in 17% and 23% patients respectively.…”
Section: Discussionsupporting
confidence: 73%
“…Sofia NH et al also found that nephrolithiasis is more common in men than in women and is more prevalent between the ages of 20 to 40 in both sexes. coffee and tea, low in fibre, vegetable protein and unrefined carbohydrates are at increased risk of kidney stones, 20 our study also found that high salt, coffee and tea intake and non vegetarian diet, less intake of water is also common risk factors for urolithiasis. Similar to other studies, [19][20][21] we also found that Diabetic and Hypertension were other risk factors for renal calculi present in 17% and 23% patients respectively.…”
Section: Discussionsupporting
confidence: 73%
“…Those with hypertension are more likely to develop kidney stones, especially when they are overweight. [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…45 Thus a high sodium intake and high BP may increase the risk of developing osteoporosis. 41,45 To support this view are the recent findings that the prevalence and incidence of kidney stones seem to be increased in people with hypertension, [60][61][62][63] that bone density is lower in elderly females at the higher end of the BP distribution than those at the lower end, 64 and that bone mineral density is associated with levels of salt intake in both young 65 and old 66 women. From the values calculated in this study, the additional calcium lost in the urine if sodium intake was increased by 100 mmol per day for 10 years would be equivalent to approximately 10% of total body calcium.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 99%